Circulating and Tissue Expression Profile of MicroRNAs in Primary Hyperparathyroidism Caused by Sporadic Parathyroid Adenomas. (3rd December 2020) - Yavropoulou, Maria P; Pazaitou‐Panayiotou, Kalliopi; Yovos, John G; Poulios, Christos; Anastasilakis, Athanasios D; Vlachodimitropoulos, Dimitris; Vamvakidis, Kyriakos; Tsave, Olga; Chrisafi, Sofia; Daskalaki, Emily; Makras, Polyzois
ABSTRACT: We investigated the expression profile of selected microRNAs (miRs) in serum and tissue samples from patients with sporadic parathyroid adenomas (sPAs). This was a prospective, controlled cohort study. Forty patients with sPAs who had undergone parathyroidectomy (PTX) were included. MiR extraction was performed from (i) 40 formalin‐fixed paraffin‐embedded samples (FFPEs) of sPAs, (ii) 10 FFPEs of normal parathyroid tissue (NPT), (iii) serum samples of the 40 patients with sPAs (t1 = baseline; t2 = 2 months post‐PTX), and (vi) serum samples of 10 healthy individuals (controls; t1 = baseline and t2 = 2 months later). Ten miRs were selected based on their interaction with genes related to parathyroid tumorigenesis (miR‐17‐5p, miR‐24‐3p, miR‐29b‐3p, miR‐31‐5p, miR‐135b‐5p, miR‐186‐5p, miR‐195‐5p, miR‐330‐3p, miR‐483‐3p, and miR‐877‐5p). At tissue level, the relative expression of miR‐17‐5p, miR‐31‐5p, miR‐135b‐5p, miR‐186‐5p, and miR‐330‐3p was significantly decreased (fold change [FC]: 0.17, FC: 0.03, FC: 0.01, FC: 0.10, FC: 0.10, respectively; all p values <0.001), and the expression of miR‐24‐3p and miR‐29b‐3p was significantly increased (FC: 12.4, p < 0.001; FC: 18.5, p = 0.011, respectively) in sPA compared with NPT samples. The relative expression of miR‐135b‐5p was also significantly decreased in the serum samples of patients compared with controls (FC: 0.7, p = 0.035). No significant differences were found in the serum samples of patients before and after PTX. MiRs that regulate genes linked to parathyroid tumors such as menin 1 (miR‐24‐3p, miR‐29b‐3p), cyclin D1 (miR‐17‐5p), calcium sensing receptor (miR‐31‐5p, miR‐135b‐5p), cyclin‐dependent kinase inhibitors (miR‐186‐5p), and β‐catenin (miR‐330‐3p) were significantly deregulated in sPAs compared with NPT samples, suggesting a role for epigenetic changes in parathyroid tumorigenesis. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.